Butterfly - Crossley, Heather; Sofroniou, Miranda (London dorling kindersley limited, 2022)
How does a tiny caterpillar turn into a beautiful butterfly? Peek under the flaps to find out!
Scientific notions
Keywords: Board books; Butterflies Life cycles; Stories in rhyme